Effect of serotonin on myocardial contractility in newborn rats with excess and deficiency of serotonin in the embryonic period - Akhmetova М.Zh.; Nigmatullina, R.R.; Mindubayeva F.А.; Tykezhanova G.М. (Fundamental and Experimental Biology, 2021)
Serotonin as a neurotransmitter (5-HT) plays a crucial role in the cardiovascular system. Serotonin is a humoral system of regulators and modulators of physiological processes. Under pathological conditions, these processes can turn into factors contributing to the development of diseases such as atherosclerosis, arterial hypertension, and pulmonary hypertension. The 5-HT4 and 5-HT2B receptors are found in cardiomyocytes. During the embryonic period, serotonin acts as a growth factor and plays an important regulatory role in the crucial period of embryonic development, in particular, a heart of an embryo. Therefore, any interference with this system in the womb can disrupt the normal development of the cardiovascular system. In the given study, there is some data provided to indicate that a change in the serotonin concentration created by the sero-tonin synthesis and the membrane serotonin transporter blocked in the embryonic period of ontogenesis, af-fects the inotropic function of the right ventricular myocardium in early postnatal ontogenesis, which is caused by a change in the contraction time in the groups under the experiment. Thus, statistically the response of cardiomyocytes to serotonin is significantly higher in the group with an excess of serotonin and signifi-cantly lower in the group with a deficiency of serotonin compared to the control group.